Red Light Controls Adventitious Root Regeneration by Modulating Hormone Homeostasis in Picea abies Seedlings - Alallaq, Sanaria; Ranjan, Alok; Brunoni, Federica; Novák, Ondřej; Lakehal, Abdellah; Bellini, Catherine (Frontiers in Plant Science, 2020)
Vegetative propagation relies on the capacity of plants to regenerate de novo adventitious roots (ARs), a quantitative trait controlled by the interaction of endogenous factors such as hormones and environmental cues among which light plays a central role. However, the physiological and molecular components mediating light cues during AR initiation (ARI) remain largely elusive. Here, we explored the role of red light on ARI in de-rooted Norway spruce seedlings. We combined hormone metabolism and gene expression analysis to identify potential signaling pathways. We also performed extensive anatomical characterization to investigate ARI at the cellular level. We showed that in contrast to white light, red light promoted ARI likely by reducing jasmonate (JA) and JA-isoleucine biosynthesis and repressing the accumulation of isopentyl-adenine-type cytokinins. We demonstrated that exogenously applied JA and/or CK inhibit ARI in a dose-dependent manner and found that they possibly act in the same pathway. The negative effect of JA was confirmed at the histological level. We showed that JA represses the early events of ARI. In conclusion, RL promotes ARI by repressing the accumulation of the wound-induced phytohormones JA and CK.